2016
DOI: 10.1002/2015rg000514
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances quantifying the large wood dynamics in river basins: New methods and remaining challenges

Abstract: Large wood is an important physical component of woodland rivers and significantly influences river morphology. It is also a key component of stream ecosystems. However, large wood is also a source of risk for human activities as it may damage infrastructure, block river channels, and induce flooding. Therefore, the analysis and quantification of large wood and its mobility are crucial for understanding and managing wood in rivers. As the amount of large-wood-related studies by researchers, river managers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
194
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(233 citation statements)
references
References 275 publications
10
194
1
Order By: Relevance
“…Figure 9. This study is notable due to the length and magnitude of the flood, something not shared by the other LW transport studies to date (Ruiz-Villanueva et al, 2016a). The figure demonstrates the two orders of magnitude increase in LW in the Lake Oahe slackwater and the likely majority source of LW 30 to 100 km upstream.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Figure 9. This study is notable due to the length and magnitude of the flood, something not shared by the other LW transport studies to date (Ruiz-Villanueva et al, 2016a). The figure demonstrates the two orders of magnitude increase in LW in the Lake Oahe slackwater and the likely majority source of LW 30 to 100 km upstream.…”
Section: Discussionmentioning
confidence: 59%
“…LW accumulation and dynamics are important for river management and science for a number of reasons including as productive habitat for aquatic organisms, an influence on channel dynamics and island formation, navigation and recreational risks, and as a nutrient exchange substrate (Ruiz-Villanueva et al, 2016a). LW accumulation and dynamics are important for river management and science for a number of reasons including as productive habitat for aquatic organisms, an influence on channel dynamics and island formation, navigation and recreational risks, and as a nutrient exchange substrate (Ruiz-Villanueva et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…3). To put this value into perspective, the volume of large wood measured within the channel after the event accounts for only 0.3 m 3 hectare −1 of sur- veyed channel area (mean log length and diameter of 1.53 and 0.08 m, respectively), which is well below other values available in the literature for basins of comparable size (see Ruiz-Villanueva et al, 2016). All evidence thus suggests that this was an extreme high-magnitude event, and that virtually all transported logs were recruited from upstream reaches or mass wasting processes at the basin scale, making the estimation of large-wood transport from in-channel large-wood deposition very difficult in these conditions.…”
Section: Resultsmentioning
confidence: 79%
“…WLF and CWT) and assuming that a third of the cross section was occupied by water, the estimated volume of transported wood is around 3680 m 3 . This volume is remarkably high, provided that in a recent review, Ruiz-Villanueva et al (2016) reported that large wood exported from basins > 100 km 2 generally ranges from 500 to 4000 m 3 (Fig. 3).…”
Section: Resultsmentioning
confidence: 97%
“…Logjams are also an important component of river ecosystems, as they influence the transfer of solutes, mineral sediment, and organic material within the river channel system and between the river and the floodplain (Coe et al, 2009;Gurnell et al, 2002;Jochner et al, 2015;Wohl and Beckman, 2014). Despite the fact that logjams can have a dramatic impact on fluvial dynamics and fluvial-floodplain exchanges, their systematic study is relatively recent and has mostly been carried out in temperate zones (Dixon, 2016;Ruiz-Villanueva et al, 2016;Wohl, 2017Wohl, , 2013. Very few studies have looked at the wood-river interactions in the neotropics, and these have mostly focused on headwater rivers Wohl, 2011, 2010;Iroumé et al, 2015;Wohl et al, 2012).…”
Section: Introductionmentioning
confidence: 99%